(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The coronavirus has magnified existing racial injustices and educational inequities. Philanthropy will play a key role in facilitating higher education’s recovery from the pandemic, but its relationship with the field needs to evolve so it can enact a more equitable and sustainable future. Informed by 30 responses from grantee partners (e.g., college leaders, scholars, research organizations, and community-based nonprofits), one foundation is on a journey to ensure that its relationships with the field are grounded in a deep understanding of partners’ needs during the pandemic and their continued service to America’s most marginalized college students. This essay features what the foundation has learned as a result of its grantees’ persistence and the actions it will undertake to further support educational equity.